PELAKSANAAN PEMBERIAN RESTITUSI TERHADAP ANAK KORBAN PENCABULAN DI PENGADILAN NEGERI BUKITTINGGI - Ihsan Kamil; Erry Gusman; Yenny Fitri Z (Ensiklopedia of Journal, 2023)
Being a victim of sexual abuse is something that no one ever wants because it is a very inhumane act, including the category of human rights violations that should receive legal protection and freedom in all fields. From a regulatory point of view, punishment for perpetrators has been regulated in law and for victims there is a need for protection. One form of legal protection for child victims of criminal acts of obscenity is to get restitution. Restitution or compensation is a fee paid by someone because of a loss suffered by another person economically. The purpose of this study is to find out how the implementation of the granting of Restitution to child victims of sexual abuse, the type of research used is empirical legal research, because empirical legal research looks at law in a real sense and examines the law in society and how the law relates to society. It can also be said that empirical research is taken from facts that exist in a society, legal entity or government agency. The data processing technique used in this study was carried out through stages, including data checking techniques, data tagging, or data systematization.